Vectorizing agrochemicals: enhancing bioavailability via carrier‐mediated transport. Issue 6 (30th January 2019) - Wu, Hanxiang; Xu, Hanhong; Marivingt‐Mounir, Cécile; Bonnemain, Jean‐Louis; Chollet, Jean‐François
Abstract: Systemicity of agrochemicals is an advantageous property for controlling phloem sucking insects, as well as pathogens and pests not accessible to contact products. After the penetration of the cuticle, the plasma membrane constitutes the main barrier to the entry of an agrochemical into the sap flow. The current strategy for developing systemic agrochemicals is to optimize the physicochemical properties of the molecules so that they can cross the plasma membrane by simple diffusion or ion trapping mechanisms. The main problem with current systemic compounds is that they move everywhere within the plant, and this non‐controlled mobility results in the contamination of the plant parts consumed by vertebrates and pollinators. To achieve the site‐targeted distribution of agrochemicals, a carrier‐mediated propesticide strategy is proposed in this review. After conjugating a non‐systemic agrochemical with a nutrient (α‐amino acids or sugars), the resulting conjugate may be actively transported across the plasma membrane by nutrient‐specific carriers. By applying this strategy, non‐systemic active ingredients are expected to be delivered into the target organs of young plants, thus avoiding or minimizing subsequent undesirable redistribution. The development of this innovative strategy presents many challenges, but opens up a wide range of exciting possibilities. © 2018 Society of Chemical Industry Abstract : Non‐systemic agrochemicals conjugated to an α‐amino acid or glucose can cross the plasma membrane via an active transport mechanism to be transported at long distance in the phloem sap flow.